WALL-E'S SELF EXISTENCE TO SAVE THE LAST PLANT IN THE EARTH IN ANDREW STANTON'S WALL-E MOVIE (2008): AN EXISTENTIALIST APPROACH - GUSNIADI, WIWIT (2011)
The major problem of this study reveal how Wall-E self existence save the last plant in the earth in Andrew Stanton's Wall-E. The objective of this study is to analyze the movie based on its structural elements and an existentialist approach. In analysis, the writer uses qualitative method. The object of the study is Wall-E released in 2008 in the United States. The data sources consist of primary and secondary data source. The primary data source is Wall-E movie and the secondary data sources are the other sources related to the primary data such as the information about director's biography and websites. The method of the data collection are watching the movie, taking notes the important data, arranging the data based on category of elements of literature review, and the last is looking for the supporting data. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusion. First, Andrew Stanton wants to tell us about the dangerous if we are not keeping our environment. Second, this movie contains unique love of the major character. And the third, the movie tells us to prioritize other interesting thing than our self thing.